Process for efficiently purifying vein quartz through gravity scrubbing and ultrasonic dissociation
By introducing gravity scrubbing and ultrasonic dissociation technologies into the vein quartz sand purification process, the problems of difficult dissociation of impurities of monomer particles and high equipment operation cost are solved, efficient purification and purity improvement are achieved, and production efficiency and pass rate are significantly improved.
Patent Information
- Application Number
- CN202510061451.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when purifying vein quartz sand, monomer particles are difficult to dissociate impurities, equipment operating costs are high, and particle size is difficult to accurately control, resulting in a low pass rate.
Gravity scrubbing and ultrasonic dissociation are used to optimize the acid leaching and flotation processes, and gravity scrubbing is used to remove most impurities on the surface of quartz sand. Ultrasonic dissociation further removes fine impurities and improves the efficiency of impurity dissociation.
It significantly improves the efficiency of impurity dissociation, reduces equipment operating costs and energy consumption, simplifies operating procedures, improves production efficiency and purity, and meets the needs of high-purity quartz products.
Smart Images

Figure CN119869741A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz sand purification and processing, and in particular to a process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation. Background Art
[0002] High-purity quartz is an important support for emerging strategic industries, but the current domestic high-purity quartz is far from meeting the needs. In particular, high-end products mainly rely on imports from the United States and Norway, which poses a great risk factor. Due to the scarcity of resources, natural crystal is no longer suitable for use as a high-purity quartz raw material for large-scale industrial applications. The remaining high-purity quartz raw materials that can be used to make high-purity quartz, especially crucible sand, are mainly concentrated in two types of minerals: granite pegmatite quartz (such as the high-purity quartz mines of Unimin in the United States and TQC in Norway) and vein quartz (such as some high-purity quartz mines in India). Among them, vein quartz has relatively abundant reserves and high economic benefits, and has gradually received attention.
[0003] The distribution of impurities in inclusions in natural vein quartz ores is often scattered and irregular. After water quenching and mechanical crushing, a large number of impurities that are difficult to separate remain on the surface of the quartz sand, which are difficult to dissociate using a single physical or chemical method. Considering the strict requirements for particle size of high-purity quartz products, if the quartz monomer cannot be completely dissociated from the impurities at a limited particle size or the dissociation degree does not meet the requirements, it will pose a major challenge to the subsequent purity or application performance. Therefore, vein quartz ores often have the lowest dissociation degree compared to granite pegmatite and quartzite. During the purification process, it is necessary to ensure the yield while solving problems such as incomplete dissociation of monomer minerals, high acid consumption, and complex processing.
[0004] The traditional high-purity quartz sand preparation method includes coarse crushing, calcination and water quenching, crushing, acid washing, flotation, drying and magnetic separation, which can remove impurities on the surface of quartz and gangue minerals associated with quartz. Among them, the flotation process can effectively separate impurity minerals in vein quartz, especially feldspar. Zhang, H. et al. treated vein quartz by crushing, grinding, calcination and quenching, acid leaching, wet high-intensity magnetic separation (WHIMS) and reverse flotation and found that about two-thirds of the aluminum impurities in the sample were dispersed in the quartz lattice and difficult to remove by traditional physical beneficiation methods. The remaining discrete aluminum impurities can theoretically be removed by traditional beneficiation technology, but the reverse flotation experiment failed to effectively remove these discrete aluminum-containing minerals, which may be due to insufficient dissociation (Zhang, H.; Dzemua, GL; Liu, Q. Preliminary Beneficiation Studies of Quartz Samples from the Northwest Territories, Canada. Minerals 2024, 14, 1177). Acid leaching is also a key step in the purification process to dissociate and remove impurity elements. Recently, researchers have developed a variety of technologies to enhance the leaching process: microwave-assisted leaching can accelerate the dissolution of gas-liquid inclusions, but at the cost of high energy consumption; multi-thermal shock leaching increases the density of cracks on the mineral surface, but the operation process is more complicated; hot pressure leaching is more efficient, but it needs to be carried out under more stringent conditions; and ultrasound-assisted leaching is recognized for its advantages of accelerating reaction speed and reducing acid consumption, but its processing capacity is limited and there are challenges in expanding its application scale. Summary of the invention
[0005] The present invention aims to provide a process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation, and aims at the problems that the monomer particle impurities are difficult to dissociate in the process of preparing high-purity quartz sand from vein quartz ore by traditional methods, the equipment operation cost is high, and it is difficult to accurately control the particle size, which reduces the qualified rate in actual use. By optimizing the acid leaching and flotation processes, the impurity dissociation efficiency is improved by using the simple physical methods of gravity scrubbing and ultrasonic dissociation.
[0006] The specific technical solutions adopted are as follows:
[0007] A process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation comprises the following steps:
[0008] (1) Pretreatment: The raw ore is coarsely crushed, and then the visible impurities in the quartz ore are removed by manual selection for rough selection. The obtained ore is then calcined, water quenched, crushed, screened, and dried in sequence;
[0009] (2) Gravity scrubbing: The quartz sand obtained in step (1) is placed in a large reactor that is slowly turned upside down. The sand particles are continuously rubbed against each other under the action of their own weight and a small amount of flowing acid to remove most of the impurities on the surface of the quartz sand;
[0010] (3) Ultrasonic dissociation: The quartz sand treated in step (2) is combined with pure water and subjected to ultrasonic vibration of an ultrasonic cleaning machine to peel off or loosen impurities (such as mica and feldspar) attached to the surface of the sand particles, further removing fine impurities remaining on the surface and promoting the subsequent reverse flotation impurity separation efficiency;
[0011] (4) Step-by-step reverse flotation: The quartz sand treated in step (3) is subjected to a two-step flotation process, wherein a cationic collector is used in an acidic solution in the first stage of flotation to remove mica minerals, and an anionic collector is used in an alkaline solution in the second stage of flotation to remove feldspar minerals such as iron and titanium;
[0012] (5) Vacuum drying: placing the quartz sand treated in step (5) into a drying kettle and heating and drying it in a vacuum state;
[0013] (6) Magnetic separation: The quartz sand treated in step (6) is subjected to magnetic separation to remove the magnetic substances contained in the quartz sand, and finally high-purity quartz sand is obtained.
[0014] Preferably, in step (1), the calcination temperature is 1050° C., the calcination time is 10-15 minutes, and quartz sand with a mesh size of 80-220 is obtained after crushing and screening.
[0015] Preferably, in step (2), the volume of the reactor is 2000L, the turning speed is 90 seconds / revolution, the scrubbing acid solution is a combination of two or three of hydrochloric acid, hydrofluoric acid and nitric acid, the concentrations of the hydrochloric acid, hydrofluoric acid and nitric acid used are all 10-40%, the scrubbing time is 18-30 hours, the scrubbing temperature is 60-75°C, the weight of the quartz sand is greater than 1000 kg, and the solid-liquid ratio of the mixed solution of the quartz sand and the acid solution is 1-3:1.
[0016] Preferably, in step (3), the ultrasonic dissociation time is 30-90 minutes, the applied frequency is 40 kHz, and the solid-liquid ratio after quartz sand is added to pure water is 1:2.
[0017] Preferably, in step (4), the pH regulator of the first stage reverse flotation is at least one of hydrochloric acid, hydrofluoric acid or oxalic acid, the collector is at least one of dodecylamine, rosin amine and mixed amines, and the flotation pH is 2-3; in the second stage of flotation, the pH regulator is at least one of sodium hydroxide, potassium hydroxide or ammonia water, the collector is at least one of oleic acid, sodium linoleate or sodium petroleum sulfonate, and the flotation pH is 7-10;
[0018] Preferably, in step (5), the drying temperature is 80-100° C. and the drying time is 8-12 hours.
[0019] Preferably, in step (6), magnetic separation is performed at least once at a field strength of 20000-22000 GS.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In view of the difficulty in removing impurities on the surface of vein quartz sand in the prior art and the problem that traditional purification methods are prone to damage quartz sand and reduce the particle size qualification rate, the present invention has made innovative improvements on the basis of traditional purification processes. The invention combines gravity scrubbing and ultrasonic dissociation technology to achieve efficient and gentle purification of vein quartz sand. Specifically, in a large olive-shaped reactor that slowly turns up and down, the sand particles rub against each other by their own weight and react with a small amount of flowing acid. Gravity scrubbing can effectively remove most of the impurities on the surface of the sand particles, and the process has little damage to the structure of the sand particles, thereby ensuring the particle size qualification rate. Then, high-power and long-term ultrasonic vibration is used to dissociate or loosen the small impurities that are difficult to separate attached to the surface of the sand particles, and further remove the residual impurities on the surface. The method of combining gravity scrubbing with ultrasonic dissociation not only reduces the environmental pollution and toxic waste risks that may be caused by over-reliance on traditional chemical methods, but also simplifies the operation process, avoids the use of high-energy consumption and long-term roasting equipment, and significantly improves production efficiency and reduces energy consumption, carbon emissions and the cost of using large and complex equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process step diagram of the present invention.
[0023] Figure 2 The aluminum (Al), calcium (Ca) and quartz sand obtained by pretreatment of vein quartz ore and the high-purity sand obtained in Example 2 are
[0024] Energy dispersive spectroscopy (EDS) element distribution diagram of sodium (Na) and lithium (Li). DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] like Figure 1 The figure shows the process steps of the invention, and the following embodiments are all operated according to the process steps.
[0027] The natural quartz ore sources used in the following examples are all high-quality quartz ore sources imported from Tanzania, the type is vein quartz, and the quartz content in the original ore is greater than 99%.
[0028] Implementation 1
[0029] (1) Pretreatment of quartz ore: First, the ore is coarsely crushed, and then the visible impurities in the quartz ore are removed manually to complete the rough selection; then, the ore is sent to a tubular furnace, which can realize continuous processing and heating of quartz sand, and calcined at 1050°C for about 10 minutes. After calcination, it is immediately water quenched; after water quenching, the ore is crushed using a jaw crusher and sieved to obtain quartz sand with a mesh size of 80-220.
[0030] (2) Gravity scrubbing: The quartz sand obtained in step (1) is placed in a reactor with a volume of 2000 liters, and a scrubbing acid solution of a combination of 10% hydrochloric acid and 12% hydrofluoric acid is added at the same time; the reactor is set to turn upside down at a slow speed of 90 seconds per revolution, and the entire scrubbing process is carried out at a temperature of 65°C and lasts for 24 hours. The weight of the quartz sand is greater than 1000 kg, and the volume ratio of the quartz sand and the acid solution after mixing is controlled to be 1:1.
[0031] (3) Ultrasonic dissociation: The quartz sand treated in step (2) is placed in an ultrasonic cleaning machine to dissociate impurities, wherein the ultrasonic dissociation time is 30 minutes, the applied frequency is 40 kHz, and the solid-liquid ratio after the quartz sand is added with pure water is 1:2.
[0032] (4) The ore pulp obtained after ultrasonic treatment in step (3) is adjusted to 50% quartz sand slurry, added to a flotation machine for flotation operation, hydrochloric acid is added to the ore pulp to adjust the pH value to 3.0, a collector composed of rosin amine and dodecylamine is added, and the amount of the collector added is 150 g / t. After stirring to generate foam, the foam is scraped and flotation is performed for 20 minutes; then the ore pulp is adjusted to 50% quartz sand slurry again, ammonia water is added to the ore pulp to adjust the pH value to 9.0, a collector composed of oleic acid and sodium linoleate is added, and the amount of the collector added is 150 g / t. After stirring to generate a small amount of foam, 120 g / t of foaming agent No. 2 oil is added thereto, stirred and scraped, and flotation is completed.
[0033] (5) The quartz sand treated in step (4) is placed in a drying kettle and heated and dried in a vacuum state, wherein the drying temperature is 90° C. and the drying time is 9 hours.
[0034] (6) The quartz sand treated in step (5) is subjected to magnetic separation to remove magnetic substances contained in the quartz sand, and finally high-purity quartz sand is obtained.
[0035] Implementation 2
[0036] (1) Pretreatment of quartz ore: First, the ore is coarsely crushed, and then the visible impurities in the quartz ore are removed manually to complete the rough selection; then, the ore is sent to a tubular furnace, which can realize continuous processing and heating of quartz sand, and calcined at 1050°C for about 10 minutes. After calcination, it is immediately water quenched; after water quenching, the ore is crushed using a jaw crusher and sieved to obtain quartz sand with a mesh size of 80-220.
[0037] (2) Gravity scrubbing: The quartz sand obtained in step (1) is placed in a reactor with a volume of 2000 liters, and a scrubbing acid solution of a combination of 36% hydrochloric acid and 40% hydrofluoric acid is added at the same time; the reactor is set to turn upside down at a slow speed of 90 seconds per turn, and the entire scrubbing process is carried out at a temperature of 65° C. and lasts for 24 hours. The weight of the quartz sand is greater than 1000 kg, and the volume ratio of the quartz sand and the acid solution after mixing is controlled to be 3:1; during the turning process, the quartz sand particles continue to rub against each other under the action of their own gravity, and interact with a small amount of flowing acid solution to remove impurities on the surface of the quartz sand.
[0038] (3) Ultrasonic dissociation: The quartz sand treated in step (2) is placed in an ultrasonic cleaning machine to dissociate impurities, wherein the ultrasonic dissociation time is 60 minutes, the applied frequency is 40 kHz, and the solid-liquid ratio after the quartz sand is added with pure water is 1:2.
[0039] (4) The ore pulp obtained after ultrasonic treatment in step (3) is adjusted to 50% quartz sand slurry, added to a flotation machine for flotation operation, hydrochloric acid is added to the ore pulp to adjust the pH value to 3.0, a collector composed of rosin amine and dodecylamine is added, and the amount of the collector added is 150 g / t. After stirring to generate foam, the foam is scraped and flotation is performed for 20 minutes; then the ore pulp is adjusted to 50% quartz sand slurry again, ammonia water is added to the ore pulp to adjust the pH value to 9.0, a collector composed of oleic acid and sodium linoleate is added, and the amount of the collector added is 150 g / t. After stirring to generate a small amount of foam, 120 g / t of foaming agent No. 2 oil is added thereto, stirred and scraped, and flotation is completed.
[0040] (5) The quartz sand treated in step (4) is placed in a drying kettle and heated and dried in a semi-vacuum state, wherein the drying temperature is 90° C. and the drying time is 9 hours.
[0041] (6) The quartz sand treated in step (5) is subjected to magnetic separation to remove magnetic substances contained in the quartz sand, and finally high-purity quartz sand is obtained.
[0042] Energy dispersive X-ray spectroscopy (EDS) can identify elements on the surface of quartz sand and estimate the element content based on the intensity of the color. Figure 2The energy dispersive spectroscopy (EDS) element distribution diagram of aluminum (Al), calcium (Ca), sodium (Na), and lithium (Li) of the quartz sand after pretreatment of vein quartz ore and the high-purity sand obtained in Example 2. The results show that after Example 2, the Al, Ca, Na, and Li elements in the diagram became sparse from dense, indicating that the process containing gravity scrubbing and ultrasonic dissociation removed most of the impurities on the surface of the quartz sand.
[0043] The silicon dioxide and impurity metal contents of the high-purity quartz sand prepared in Example 2 were analyzed and detected by ICP-MS. The results are shown in Table 1. The total amount of impurity elements is 23.35 ppm, which proves that the purity of vein quartz can be improved by adjusting experimental conditions such as physical scrubbing and ultrasound, and can meet the current demand for quartz products such as quartz crucibles, quartz drawn tubes, and quartz ingots, and expand the application of silicon-based raw materials in photovoltaics, semiconductors, electric light sources, optics, and electronic communications.
[0044] Table 1 Impurity content in the product quartz sand in the embodiment (ppm)
[0045]
[0046] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation, characterized in that: The following steps are involved: (1) Pretreatment: The raw ore is coarsely crushed, and then the visible impurities in the quartz ore are removed by manual selection for rough selection. The obtained ore is then calcined, water quenched, crushed, screened, and dried in sequence; (2) Gravity scrubbing: The quartz sand obtained in step (1) is placed in a large reactor that is slowly turned upside down. The sand particles are continuously rubbed against each other under the action of their own weight and a small amount of flowing acid to remove most of the impurities on the surface of the quartz sand; (3) Ultrasonic dissociation: The quartz sand treated in step (2) is combined with pure water and subjected to ultrasonic vibration of an ultrasonic cleaning machine to peel off or loosen impurities (such as mica and feldspar) attached to the surface of the sand particles, further removing fine impurities remaining on the surface and promoting the subsequent reverse flotation impurity separation efficiency; (4) Step-by-step reverse flotation: The quartz sand treated in step (3) is subjected to a two-step flotation process, wherein a cationic collector is used in an acidic solution in the first stage of flotation to remove mica minerals, and an anionic collector is used in an alkaline solution in the second stage of flotation to remove feldspar minerals such as iron and titanium; (5) Vacuum drying: the quartz sand treated in step (4) is placed in a drying kettle and heated and dried in a vacuum state; (6) Magnetic separation: The quartz sand treated in step (5) is subjected to magnetic separation to remove the magnetic substances contained in the quartz sand, and finally high-purity quartz sand is obtained.
2. A process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation according to claim 1, characterized in that: In step (1), the calcination temperature is 1050° C., the calcination time is 10-15 minutes, and the quartz sand with a mesh size of 80-220 is obtained after crushing and screening.
3. The process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation according to claim 1 is characterized in that: In step (2), the volume of the reactor is 2000L, the turning speed is 90 seconds / revolution, the scrubbing acid solution is a combination of two or three of hydrochloric acid, hydrofluoric acid and nitric acid, the concentrations of the hydrochloric acid, hydrofluoric acid and nitric acid used are all 10-40%, the weight of the quartz sand is greater than 1000 kg, the scrubbing time is 18-30 hours, the scrubbing temperature is 60-75°C, and the solid-liquid ratio of the mixed solution of the quartz sand and the acid solution is 1-3:
1.
4. The process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation according to claim 1 is characterized in that: The ultrasonic dissociation time in step (3) is 30-90 minutes, the applied frequency is 40 kHz, and the solid-liquid ratio after the quartz sand is added to pure water is 1:
2.
5. The process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation according to claim 1 is characterized in that: In step (4), the pH regulator of the first stage reverse flotation is at least one of hydrochloric acid, hydrofluoric acid or oxalic acid, the collector is at least one of dodecylamine, rosin amine and mixed amines, and the flotation pH is 2-3; in the second stage of flotation, the pH regulator is at least one of sodium hydroxide, potassium hydroxide or ammonia water, the collector is at least one of oleic acid, sodium linoleate or sodium petroleum sulfonate, and the flotation pH is 7-10.
6. The process for efficiently purifying vein quartz by gravity scrubbing and ultrasonic dissociation according to claim 1 is characterized in that: In step (5), the drying temperature is 80-100° C. and the drying time is 8-12 hours.